2021
DOI: 10.1088/1361-6528/ac2c44
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen vacancies boosted vanadium doped ZnO nanostructures-based voltage-switchable binary biosensor

Abstract: The development of a reliable non-enzymatic multi-analyte biosensor is remained a great challenge for biomedical and industrial applications. In this prospective, rationally designed electrode materials having voltage switchable electrocatalytic properties are highly promising. Here, we report vanadium doped ZnO engineered nanostructures (Zn 1−x V x O where 0x0.1) which exhibit voltage switchable electrocatalytic properties for accurate measurements of glucose and hydrogen peroxide. Microstructures and che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 64 publications
4
4
1
Order By: Relevance
“…The close observation shows that Au 4f peaks shift ∼ 0.68 eV towards negative side which ascribed to the electron transfer from Au QDs to ZnO due to their strong interaction. These results agree well with our previous observation as well as reported by Bai et al [26][27][28] O v ). The intensity ratio of O V peak to O L peak (0.49) of O 1s spectra of ZnO@Au QDs (0.6) structure displays an increased amount of oxygen defects compared to other products as shown in Figure S2(a-c).…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…The close observation shows that Au 4f peaks shift ∼ 0.68 eV towards negative side which ascribed to the electron transfer from Au QDs to ZnO due to their strong interaction. These results agree well with our previous observation as well as reported by Bai et al [26][27][28] O v ). The intensity ratio of O V peak to O L peak (0.49) of O 1s spectra of ZnO@Au QDs (0.6) structure displays an increased amount of oxygen defects compared to other products as shown in Figure S2(a-c).…”
Section: Resultssupporting
confidence: 94%
“…The difference between peaks is 23.28 eV, which satisfied the standard value of 22.97 eV. [26] Figure 5(c) reveals the high resolution XPS spectrum in the binding energy range of 80-100 eV. The fitting spectrum consists of two significant binding energy peaks at 83.05 and 86.5 eV corresponding to the electronic states of Au 4f 7/2 and Au 4f 5/2 respectively.…”
Section: Resultssupporting
confidence: 59%
“…3(c). The binding energy difference between two peaks is slightly higher as compared to previous reports, 59 which is due to the interactions between ZnO andMoS 2 in the heterostructure. Fig.…”
Section: Resultscontrasting
confidence: 56%
“…It has been reported that the mesoporous nanostructures increase the electrochemically active sites as well as surface area and play a significant role in the construction of non-enzymatic electrodes for cholesterol detection [ 104 ]. The defects in nanostructures lead to the delocalization of electron distribution and promotion of electron excitation responsible for fast charge transportation and increased conductivity [ 105 ]. The electrochemically active sites of the hybrid structures result in a high sensitivity, which makes them a potential candidate for the construction of cost-effective electrochemical biosensors [ 106 ].…”
Section: Strategies To Enhance the Performance Of A Biosensormentioning
confidence: 99%